Acculturation and Psychological Adaptation - Smith Castro, Vanessa (2003)
This volume addresses the psychological impact of interethnic contact and acculturation in Latin American settings, focusing on the effects of acculturation on self-esteem among adolescents. Opening with an account of relevant theoretical and empirical literature on interethnic contact and acculturation, this book represents an acid test of the cross-cultural applicability of theory and method largely derived from research on acculturation to North American and European settings. Much research has focused on acculturation processes among ethnic immigrants and ethnic minorities leading to the impression that host or majority groups remain unchangeable during acculturation. By contrast, this volume shows that psychological changes occur in all groups involved in the contact, reinforcing the idea that acculturation is a special case of mutual influence. This book will be of special interest for researchers, scholars or students seeking to understand the acculuturation process outside North America and Europe. Strong evidence is pressented showing the development of positive ties with both one's own and other relevant groups provides a more solid basis for self-esteem than relinquishing ties to the ethnic group of reference.